(untitled) (The Pakistan Development Review, 2025)
The proposed research project is based on a multidisciplinary approach in order to analyse the law governing the sugar industry and the implications thereof. The proposed research project focuses on the current market operation within Pakistan, critically contrasting it with the model implemented within different jurisdictions for effective market operation of the sugar industry. It highlights the inefficaciousness and longstanding practices of the market players, how these are supported by existing legal structures, and how these undermine competition. While the sugar industry is highly significant towards the economy of Pakistan and regardless of the so-called stringent legislative control, which have without a doubt failed, this study shall focus on unveiling the adverse implications of these rules and regulations and analyse a more viable model for an effective market operation. INTRODUCTION The sugar industry plays a crucial role in Pakistan’s economy, but government regulations have made it highly regulated, inefficient, and anti-competitive. This article explores the historical development of the sugar industry in Pakistan, focusing on the legislative framework that has shaped it up to 2021. It considers relevant laws, case law, and findings from the Sugar Inquiry Report (Sugar Inquiry Commission, 2020). To gain a comprehensive understanding, the study includes key informant interviews with stakeholders along the sugar supply chain and experts. These interviews assess the proposed reforms’ prudency, efficiency, and adequacy, aiming to determine their effectiveness and viability. Ultimately, the article will propose reforms tailored to Pakistan based on this research. PRE-PARTITION From the late 1800s to the early 1930s, the sugar industry in the Dutch East Indies, particularly on the island of Java, went through significant developments. Initially, sugar was a crucial export commodity for the colony, primarily directed towards European markets. However, in the 1880s, the Java-based sugar factories lost contact with these markets. Around the turn of the 20th century, the United States became a major recipient of Java’s sugar exports due to disruptions in Caribbean sugar supplies caused by the Cuban revolution and the Spanish-American war. However, by the early 1910s, Java shifted its focus to Asian markets, particularly the Indian Subcontinent, China, and Japan (Knight, 2010). The development and maintenance of the sugar industry became crucial for the Indian subcontinent, and historical records indicate that India had a well-established sugar industry dating back centuries. Around the same time, with the decline of indigo cultivation in North Bihar and increased emphasis on cane production, modern sugar factories began to emerge.